2008
DOI: 10.1291/hypres.31.1007
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Treatment with .ALPHA.-Tocopherol Improves Erectile Function in Hypertensive Rats

Abstract: There is no known treatment for erectile dysfunction (ED) in hypertensive patients. We tested whether or not antioxidative therapy improves ED in the setting of hypertension. Spontaneously hypertensive rats

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 14 publications
1
13
1
4
Order By: Relevance
“…The intracavernosal pressure increase induced by pelvic nerve stimulation was augmented and nNOS and eNOS expression levels in the corpus cavernosum were increased in the SHR treated with a herbal formulation consisting of the seeds of Lycium chinense, Cornus officinalis, Rubus coreanus, and so on, compared with the nontreated SHR [111]. Relaxations in response to electrical field stimulation of the corpus cavernosum were improved and tissue cyclic GMP levels were greater in SHRs fed a-tocopherol compared with the controls; this treatment also decreased thiobarbituric acid-reacting substance levels and increased superoxide dismutase activity in the serum and corpus cavernosum [112]. The antioxidant therapy may contribute to improve the penile erectile function in hypertensive patients.…”
Section: Antihypertensive Therapy In Relation To Neuronal Nitric Oxidmentioning
confidence: 92%
“…The intracavernosal pressure increase induced by pelvic nerve stimulation was augmented and nNOS and eNOS expression levels in the corpus cavernosum were increased in the SHR treated with a herbal formulation consisting of the seeds of Lycium chinense, Cornus officinalis, Rubus coreanus, and so on, compared with the nontreated SHR [111]. Relaxations in response to electrical field stimulation of the corpus cavernosum were improved and tissue cyclic GMP levels were greater in SHRs fed a-tocopherol compared with the controls; this treatment also decreased thiobarbituric acid-reacting substance levels and increased superoxide dismutase activity in the serum and corpus cavernosum [112]. The antioxidant therapy may contribute to improve the penile erectile function in hypertensive patients.…”
Section: Antihypertensive Therapy In Relation To Neuronal Nitric Oxidmentioning
confidence: 92%
“…Chez l'animal, il a été mis en évidence une augmentation du stress oxydatif ainsi que la fabrication de ROS [23]. La nicotinamide adénine dinucleotide phosphate (NADPH) oxydase serait en partie responsable de la production de ROS et des altérations de la SOD [24,25]. Chez le rat hypertendu atteint de dysfonction érectile, il a été mis en évidence une diminution de l'activité de la SOD entraî-nant une augmentation des ROS dans les tissus caverneux.…”
Section: L'hypertension Artérielleunclassified
“…Chez le rat hypertendu atteint de dysfonction érectile, il a été mis en évidence une diminution de l'activité de la SOD entraî-nant une augmentation des ROS dans les tissus caverneux. [25] L'hypercholestérolémie L'hypercholestérolémie est considérée comme un facteur de risque indépendant de dysfonction érectile [26]. Deux études ont démontré que l'hypercholestérolémie entraînait une diminution de l'activité de la eNOS et de la production de eNO provoquant une nette diminution de la vasoactivité des corps caverneux [27,28].…”
Section: L'hypertension Artérielleunclassified
“…A growing number of research has indicated that antioxidants can improve ED [7,12,13,14,15]. The purpose of this study was to investigate whether PNS are able to improve the erectile function of rats with DMED and whether the antioxidant effect of PNS underlies this mechanism.…”
Section: Introductionmentioning
confidence: 99%